Impact of Academic Background on Orthopaedic Foot and Ankle Fellowship Match Outcomes - Kenneth Bryan Choy DO; Lisa K. Cannada MD, FAAOS, FAOA, FACS; Peter White DO; Scott Steinmann MD, FAAOS; Randy Cohn MD, FAOA, FAAOS; Adam Bitterman DO, FAAOS (Foot & Ankle Orthopaedics)
Category: Other Introduction/Purpose: In recent years, there has been an increase in doctors of osteopathic medicine (DO) applying for orthopaedic residency, which has led to an increase in osteopathic residents applying for fellowships. The purpose of this study was to evaluate the change in degree type of applicants to foot and ankle fellowships over the last 12 years and to evaluate the differences in match rates between osteopathic and allopathic applicants. Methods: SF Match data from 2012 to 2023 was analyzed. There were 1082 applicants for adult foot and ankle fellowships from 2012-2023. There were 74 osteopathic applicants (11.4%) and 573 allopathic applicants (88.6%). There were 435 (40.2%) international medical graduates who were excluded from this analysis. The degree type, number of applicants, and number of matched applicants into orthopaedic foot and ankle fellowship was reviewed. Trends regarding number of applicants and match rates based on applicant degree were evaluated. Results: Osteopathic applicants ranged from a low of 2 in 2018 to a high of 11 in 2016, (mean 6.2 +/- 2.6), with no statistically significant change (r=-0.12, p=0.34). Match rate for osteopathic applicants increased from 75.0% (6 of 8) in 2013 to 100.0% (5 of 5) in 2023, (mean 91.2% +/- 9.9%), with a significant increase (r=0.72, p=0.003). Allopathic applicants ranged from a low of 37 in 2022 to a high of 63 in 2014 (mean 47.8 +/- 6.9), with a significant decrease (r=-0.7, p=0.003). Match rate for allopathic applicants ranged from a low of 88.0% (44 of 50) in 2013 to a high of 100.0% (37 of 37) in 2022, (mean 94.5% +/- 4.5%), with a significant increase over the study period (r=0.79, p=0.0007). Conclusion: Since 2012, there has been no statistically significant change in the number of osteopathic applicants for foot and ankle fellowship. While both osteopathic and allopathic applicants experienced a significant increase in match rates, there was no significant difference in match rates.